2021
DOI: 10.3389/fimmu.2021.734322
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Histochemical Signatures of Bone Marrow Mononuclear Cell-Mediated Resolution of Synovitis

Abstract: Osteoarthritis (OA) may result from impaired ability of synovial macrophages to resolve joint inflammation. Increasing macrophage counts in inflamed joints through injection with bone marrow mononuclear cells (BMNC) induces lasting resolution of synovial inflammation. To uncover mechanisms by which BMNC may affect resolution, in this study, differential transcriptional signatures of BMNC in response to normal (SF) and inflamed synovial fluid (ISF) were analyzed. We demonstrate the temporal behavior of co-expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 124 publications
(222 reference statements)
0
6
1
Order By: Relevance
“…PPARG signalling is involved in skeletal muscle regeneration via growth/differentiation factor 3 (GDF3) (86). PPARG expression is upregulated in synovitis, indicating its role in mediating tissue recovery (87). Although ubiquitin carboxylterminal hydrolase (UCL1), thioredoxin-interacting protein (TXNIP), and DICER1 are among the top members of the causal network, we did not find a direct association between these factors and clusterin.…”
Section: Overall Clusterin Network In the Ipa Knowledgebasecontrasting
confidence: 58%
“…PPARG signalling is involved in skeletal muscle regeneration via growth/differentiation factor 3 (GDF3) (86). PPARG expression is upregulated in synovitis, indicating its role in mediating tissue recovery (87). Although ubiquitin carboxylterminal hydrolase (UCL1), thioredoxin-interacting protein (TXNIP), and DICER1 are among the top members of the causal network, we did not find a direct association between these factors and clusterin.…”
Section: Overall Clusterin Network In the Ipa Knowledgebasecontrasting
confidence: 58%
“…Overall, our results agree with findings from an experimental model of synovial inflammation in horses, as well as clinical trials of intra-articular BMNC for OA-affected human patients ( 41–43 ). Findings from in vitro studies suggest that clinical improvements from BMNC are associated with an early pro-inflammatory response that triggers sustained increased expression of known drivers of inflammation resolution, such as IL-10, IGF-1 and peroxisome proliferator-activated receptor-gamma, and isoprenoid biosynthesis ( 40 ). However, further in vivo studies are required to explore these and other mechanisms by which BMNC drive synovial inflammation resolution.…”
Section: Discussionmentioning
confidence: 99%
“…BMNC-treated joints were histologically comparable to healthy joints while saline-treated controls remained abnormal ( 41 ). Transcriptional and histochemical investigations further revealed that BMNC induce resolution through enhanced expression of homeostatic mechanisms that combine a fine-tuned expression of pro- and anti-inflammatory mediators ( 40 ). The objective of this study was to evaluate the ability of intra-articular BMNC therapy to improve clinical signs of naturally occurring osteoarthritis in horses.…”
Section: Introductionmentioning
confidence: 99%
“…CHAMP1 encodes a protein with a function in kinetochore–microtubule attachment and in the regulation of chromosome segregation. These properties are performed by their interaction and regulation of cell structure organization preceding mitosis, both of which are known to be important for proper fetal development [ 75 , 76 ]. Moreover, proper MIPEP expression is essential to maintain the normal level of mitochondrial sirtuin 3, which is considered a key regulator of oxidative stress by the deacetylation of the substrates involved in both ROS production and detoxification [ 77 , 78 , 79 ].…”
Section: Genetic Basis Of the T13 And T18 Pathogenesesmentioning
confidence: 99%